2021
DOI: 10.1007/s12035-021-02663-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroligin-3 Regulates Excitatory Synaptic Transmission and EPSP-Spike Coupling in the Dentate Gyrus In Vivo

Abstract: Neuroligin-3 (Nlgn3), a neuronal adhesion protein implicated in autism spectrum disorder (ASD), is expressed at excitatory and inhibitory postsynapses and hence may regulate neuronal excitation/inhibition balance. To test this hypothesis, we recorded field excitatory postsynaptic potentials (fEPSPs) in the dentate gyrus of Nlgn3 knockout (KO) and wild-type mice. Synaptic transmission evoked by perforant path stimulation was reduced in KO mice, but coupling of the fEPSP to the population spike was increased, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…2E) and at excitatory synapses (Fig. 1B-C), NL3 KO caused excitatory synapse phenotypes in CA1 57,58 , dentate gyrus 59 , and stratum oriens 60 , consistent with our findings. Other studies focusing on subtype-specific phenotypes 11 and cell typespecific localization of NL3 in hippocampus 50,51 indicate more refined specificities, including at inhibitory CCK synapses, which require focused investigations into putative roles of phosphorylated NL3 at those subtypes.…”
Section: Nl3 Specificities In Mouse Models Of Diseasesupporting
confidence: 91%
“…2E) and at excitatory synapses (Fig. 1B-C), NL3 KO caused excitatory synapse phenotypes in CA1 57,58 , dentate gyrus 59 , and stratum oriens 60 , consistent with our findings. Other studies focusing on subtype-specific phenotypes 11 and cell typespecific localization of NL3 in hippocampus 50,51 indicate more refined specificities, including at inhibitory CCK synapses, which require focused investigations into putative roles of phosphorylated NL3 at those subtypes.…”
Section: Nl3 Specificities In Mouse Models Of Diseasesupporting
confidence: 91%
“…Synaptic strength measured by the fEPSP slope is unchanged in Nlgn2 KO mice, but paired-pulse inhibition is strongly decreased and the population spike output is strongly increased, leading to an increase in network excitation (Jedlicka et al, 2011). Nlgn3 KO mice also exhibit a reduction in the fEPSP slope, but show a tendency toward increased, rather than decreased, paired-pulse inhibition; indicating that the unchanged population spike output is the result of a compensatory increase in the intrinsic excitability (Muellerleile et al, 2022). In the present work, we show that Nlgn4 KO mice exhibit no differences in excitatory synaptic transmission, a tendency toward decreased population spike output and an increase in paired-pulse inhibition (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Nlgn4 makes up only 3% of the total neuroligin protein in the adult mouse brain (Varoqueaux et al, 2006), so any differences in the Nlgn4 KO are expected to be weaker compared with other neuroligin KOs. Furthermore, it was previously shown that Nlgn1 protein expression was downregulated in hippocampal synaptosomes from Nlgn3 KO mice, which could help explain the prominent defects in excitatory synaptic transmission observed in these mice (Muellerleile et al, 2022). Since Nlgn4 does not form heterodimers with other neuroligins (Poulopoulos et al, 2012), its deletion is unlikely to directly affect the expression of other neuroligins and thus have a narrower impact compared with the deletion of neuroligins that form heterodimers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations